KEBIJAKAN FORMULASI PIDANA TERHADAP KORPORASI SEBAGAI PELAKU TINDAK PIDANA PENCUCIAN UANG DALAM UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Kristian Kristian; Christine Tanuwijaya (Universitas Suryakancana, 2016)
Globalization characterized by rapid movement of people, trade and capital information, in addition to the beneficial effects for human life must also be wary of negative side effects, namely the globalization of crime and increasing the quantity and quality of crime.Money laundering as a form of transnational and systematic crimerequires states to take precautions through domestic law and require each country to adopt in accordance with the principles of its domestic law, legislative measures and other measures necessary , to handle activities that are classified in the form of money laundering.Money laundering not only threaten economic stability and integrity of the financial system, but also can harm the joints of the life of society, nation and state, today's development is quite alarming.Crime by utilizing the network of financial systems to hide the origin of money from certain criminal offenses to look like lawful money impact is not small losses can even be systemic.The crime of the canal above a certain offense that accompanies it, the crime took means or comprehensive effort in handling.Criminal in money laundering can be classified into 2 (two), namely in terms of human actors as subjects of law (support rights and obligations), and can also form a corporation.In order to tackle money laundering are two (2) steps that can be taken both penal and non-penal efforts. Speaking penal efforts must not be separated from the discussion on criminal policyas proposed by G.Peter Hoefnagels that “criminal policy is the rational organization of the social reaction to crime.In this paper, the discussion will focus on the policy of the criminal law against corporations that make money laundering based on Undang-Undang No. 8 Tahun 2010 tentang Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang.Keywords: Formulation, Corporate, Money Laundering.